Validity and safety of endoscopic biliary stenting for biliary stricture associated with IgG4-related pancreatobiliary disease during steroid therapy - Kuraishi, Yasuhiro; Muraki, Takashi; Ashihara, Norihiro; Ozawa, Makiko; Nakamura, Akira; Watanabe, Takayuki; Ito, Tetsuya; Hamano, Hideaki; Kawa, Shigeyuki (Endoscopy International Open, 2019)
Background Patients with IgG4-related sclerosing cholangitis and autoimmune pancreatitis frequently develop obstructive jaundice, which requires endoscopic biliary stenting (EBS) during steroid therapy to prevent bile duct infection from cholestasis and adverse steroid effects. However, it is controversial whether EBS during steroid therapy is advisable, because the procedure itself carries a risk of cholangitis and procedure-related adverse events. This study aimed to clarify the validity and safety of EBS for patients with biliary stricture associated with IgG4-related pancreatobiliary disease (IgG4-PBD) during steroid therapy.Methods We enrolled 59 patients who presented with biliary stricture exhibiting jaundice or liver dysfunction and who were treated with EBS. The incidences of recurrent biliary obstruction and acute cholangitis were compared for EBS cases with and without steroid administration.Results EBS was present in 55 periods with steroid administration and 110 periods without. The incidence of recurrent biliary obstruction was significantly lower in cases with steroids than in those without (1-month no obstruction rate: 100 % vs. 82 %; log-rank test P = 0.0015). The incidence of acute cholangitis related to stenting was significantly lower in cases with steroids than in those without (1-month no acute cholangitis rate: 100 % vs. 90 %; log-rank test P = 0.0278). Biliary stents could be removed without acute cholangitis, liver dysfunction, or stent replacement in 96 % of patients who underwent endoscopic retrograde cholangiopancreatography 1 month after commencing steroid administration.Conclusions EBS during steroid administration was both valid and safe in patients with biliary stricture associated with IgG4-PBD. Stents could be safely removed 1 month after steroid initiation.